ANALISIS STRATEGI PEMASARAN PADA TOKO STATIONERY EXPRESS BANJARMASIN - Prihatini Ade Mayvita; Mohammad Zainul; Arif Sidik (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2015)
Business opportunities school and office stationery nothing ever receding business development. Business diversification of business marketing efforts and school stationery, increasingly growing rapidly along with the rise of the interest of education and offices in this globalization era.The purpose of this study was to find out how much effort Stationery Stores Exspress in terms of marketing strategy, especially in terms of service improvement, and would like to illustrate the importance of competitive strategy is an effort to improve services in order to increase customer interest in order to continue running the company's survival.The method in this study is a combination of quantitative and qualitative methods using SWOT analysis and IE Matrix.The results showed that the strength of the store Stationery Express is on the price and quality of products, while weakness is the lack of consumer satisfaction (service) and media promotion is lacking. Opportunities demonstrated by the products that are easily obtainable (location), the influence of promotions and price in accordance with customer expectations. Threats facing is the quality, price, service and promotion of competition. A good marketing strategy for the Exspress Stationery store always see the market conditions patterned on the development of today's society and done konfrehensif and sustainable.The Internal-External matrix results indicate that Exspress Stationery store on the growth of the cell position, which means that the strategy should the firm is concentrating through horizontal integration stability by conducting further business development.